Beyond the Euboeans: Phoenician immigrants, italicscommunities in Pitecusa, and their contributions - Araújo de Lima, Rodrigo (Romanitas - Revista de Estudos Grecolatinos, 2025)
The present article examines the issue of the origin of Pithecusa, an ancient Greek city located on the island of Ischia, in the Gulf of Naples. It investigates the historical disputes about the city’s founders and evaluates the validity of these narratives. Over the centuries, different theories have emerged, attributing the foundation of Pithecusa to different Greek ethnic groups, such as the Euboeans or the Phoenicians. The text analyses the historical and archaeological evidence behind these theories and proposes a reflection on how to understand the complexity of ancient Pithecusa.